A Pharmacokinetic–Viral Kinetic Model Describes the Effect of Alisporivir as Monotherapy or in Combination With Peg‐IFN on Hepatitis C Virologic Response. Issue 5 (28th August 2014) - Nguyen, T H T; Mentré, F; Levi, M; Yu, J; Guedj, J
<x xml:space="preserve">Abstract</x> Alisporivir is a cyclophilin inhibitor with demonstrated in vitro and in vivo activity against hepatitis C virus (HCV). We estimated the antiviral effectiveness of alisporivir alone or in combination with pegylated interferon (peg‐IFN) in 88 patients infected with different HCV genotypes treated for 4 weeks. The pharmacokinetics of the two drugs were modeled and used as driving functions for the viral kinetic model. Genotype was found to significantly affect peg‐IFN effectiveness (ɛ = 86.3 and 99.1% for genotypes 1/4 and genotypes 2/3, respectively, P < 10−7) and the loss rate of infected cells (δ = 0.22 vs. 0.39 per day in genotype 1/4 and genotype 2/3 patients, respectively, P < 10−6). Alisporivir effectiveness was not significantly different across genotypes and was high for doses ≥600 mg q.d. We simulated virologic responses with other alisporivir dosing regimens in HCV genotype 2/3 patients using the model. Our predictions consistently matched the observed responses, demonstrating that this model could be a useful tool for anticipating virologic response and optimizing alisporivir‐based therapies. Clinical Pharmacology & Therapeutics (2014); 96 5, 599–608. doi:10.1038/clpt.2014.173